PEMETAAN AIR TANAH PADA LAHAN KERING DI RT 05 DESA MUARO PIJOAN MENGGUNAKAN METODE GEOLISTRIK KONFIGURASI WENNER - Eka Nurshafni; Faizar Farid; Samsidar Samsidar; Linda Handayani (Universitas Riau, 2019)
The Study has been done using the geoelectric wenner configuration method in Muaro Pijoan Village, District of Jambi Luar Kota, Muaro Jambi Regency. The purpose of this study were to map the resistivity and determine the ground water position in Muaro Pijoan Village. The study area is divided into 5 tracks, 2 tracks along 100 meters and 3 tracks along 200 meters. Tracks with length 100 meters has space 5 meters and the track with length 200 meters has space of 10 meters. The value obtained from the measurement is the current and potential values, the value is used to obtain the apparent resistivity. The apparent resistivity value is then inverted using Res2Dinv software into 2 dimensional form. The inversion results in 3 cross-sectional resistivity imaged with color and each color indicates a sunder ground resistivity value. Based on the rock resistivity table, ground water has a resistivity value between 30-100 Ω.m. From the cross-sectional resistivity it is found that all tracks have a potential ground water content and the location varies from 2.5 to 34.6 meters below the soil surface. The largest groundwater potential is on track 3 and the smallest is on track 5. Based on its groundwater position in Muaro Pijoan Village includes shallow groundwater.